(untitled) (The Peerian Journal, 2023)
The article presents the synthesis of an organosilicon water repellent based on vinylethynylmagnesium bromide for building materials. The reduction in water absorption as a result of the influence of a water repellent on the material is also scientifically substantiated. A comparative analysis of the synthesized water repellent with existing water repellents is described